Middle cerebral artery blood flow velocity in elite power athletes during maximal weight-lifting - Dickerman, R. D.; McConathy, W. J.; Smith, G. H.; East, J. W.; Rudder, L. (Neurological Research, 2000)
Cerebral blood flow velocity (CBFV) has been shown to significantly increase during dynamic exercise (running) secondary to increases in cardiac output. Static exercise (weight-lifting) induces supraphysiological arterial pressures up to 450/380 mmHg, and thus may alter CBFV. Catastrophic brain injuries such as stroke, cerebral hemorrhage, subarachnoid hemorrhage, retinal hemorrhage and retinal detachment have been associated with weight-lifting. A recent study has shown that intra-ocular pressure (IOP), which is an indirect measure of intracranial pressure, elevates to pathophysiologic levels during weight-lifting. Recent CBFV studies instituting Valsalva have demonstrated decreases in CBFV from 21%-52%. To date, no studies have examined CBFV during maximal weight-lifting to elucidate the cerebrovascular responses to extreme pressure alterations. We recruited nine elite power athletes, including a multi-world record holder in powerlifting, for a transcranial Doppler study of middle cerebral artery blood flow velocity at rest and during maximal weight-lifting. All subjects' resting blood flow velocities were within normal ranges (mean 64.4 +/- 9.5 cm sec2). Blood flow velocities were significantly (p < 0.0001) decreased in all subjects during maximal lifting (mean 48.4 +/- 10.1 cm sec2). Linear regression analysis demonstrated a significant inverse linear relationship in the net change of blood velocities from rest to maximal lift for each subject (r = 0.8585, p < 0.001). This study demonstrates that blood flow velocities are significantly decreased during heavy resistance training. The drop in CBFV during weight-lifting was significantly less than previous Valsalva studies, which likely reveals the cardiovascular, baroreflex, and cerebrovascular system adaptations occurring in these elite power athletes.